Identificação das espécies do complexo Candida haemulonii, Cryptococcus spp e Paracoccidiodes sp por espectrometria de massas MALDI-TOF - Carvalho, Rafaella Grenfell de [UNIFESP] (2016)
AIMS: 1.) Describe the identification performance of the platforms and assess to the ribosomal protein expression for the species of the complex C. haemulonii. 2.) Analyze the interference of polysaccharide capsule for the identification of Cryptococcus species. 3.) Analyze the expression of ribosomal proteins between the species of Paracoccidíoides. Methods: For the complex of C. haemuloníi 29 clinical samples were analyzed, they were subjected to sequencing of the ITS region and extraction of ribosomal proteins with formic acid and acetonitrile for analysis by MALDITOF. The sequence data were compared with the NCBI BLAST platform site. Data extraction were compared with Biotyper database, and analyzed by FlexAnalysis and ClinProTools. The analysis ofthe interference ofthe polysaccharide capsule was done with eight genotypes of Cryptococcus, cultivated in different media (inductor capsule growth medium Sabouraud agar and reducing medium capsule) and analyzed the thickness of each genotype capsule in each type of culture medium and correlated with the identification of such genotypes by MALDI-TOF. The differentiation of the species of Paracoccidioides analyzes were performed by MALDI-TOF after extraction of ribosomal proteins through changes in the extraction protoco!. Results: Ali 29 samples of the complex C. haemulonii were correctly identified by sequencing and were not , correctly identified by MALDI-TOF. The species C. haemulonii and C. haemulonii var vulnera are very similar and few representative variations in their mass spectra. The thickness of the polysaccharide capsule of Cryptococcus genotypes is relevant to the quality of the spectra obtained by MALDI-TOF and the correct identification of the species. Paracoccidíoides species were correctly identified MALDI-TOF and differences were identified from the mass spectra between species. Conclusions: The sequence is the only way to correct identification of the species of the complex C. haemulonii. The distinctions between the species C. haemulonií and C. haemulonii var vulnera were scarce, but present. The reduction of Cryptococcus capsule was necessary for the correct identification of the Cryptococcus species. There were significant differences between mass spectra among Paracoccidioides species and the correct identification by MALDI-TOF was obtained.